Implementation of Islamic Economics: A Study of Pragmatic Thinking by Charles S. Peirce, Amin Abdullah, and Kim Knott - Melis; Abdullah, Amin (International Journal of Islamic Finance, 2023)
Background: As Charles S. Pierce believed in his book "Contemporary Introductions" by Milton K. Munits. According to Munitz, science's contribution to the advancement of human civilization cannot be separated. In his book Religious Studies Normativity or Historicity? Amen Abdullah noted that the pursuit of knowledge never comes to an end at any particular point but rather goes on more research and investigation are done to better understand the circumstances and conditions of human life. Novelty: The use of Maqashid Sharia in determining islamic economics ideas. Objectives: The purpose of this paper is to discuss ideas regarding current happenings. Regarding Islamic economics in Indonesia, clearly, objectively, and analytically. Present-day Islamic economics still has a conceptual and practical gap. Therefore, using an Islamic law/maqashid sharia approach to determine the meaning of economic ideas in Islam takes a while. One of the attempts to overcome the development of Islamic economic principles in the study of the philosophy of Islamic sciences Research Methodology / Design: This study uses a literature review methodology and is qualitative in nature. Findings: According to Pierce, the pragmatic approach focuses primarily on the process of scientific inquiry as well as the classification of concepts and the means by which they are believed. According to Kim Knott, the process of finding meaning involves inquiry and the participation of academics from both inside and outside groups. Implication: Dismantling critical thinking using a critical paradigm is one of the methods used in studying the philosophy of Islamic sciences to impede the growth of Islamic economic conceptions and thought.